Arc Welding-Laser Shock Forging Process for Improving the Mechanical Properties of the Fe-Cr-C Cladded Layer. (10th November 2021) - Fan, Yunpeng; Zhang, Chong; He, Hongtao; Zhang, Fengwei; Zhang, Yongkang
Abstract : While parts can be repaired via arc welding (AW), it is usually necessary to add some types of excitation method to improve the mechanical properties of the cladded layer. Here, the arc welding-laser shock forging (AW-LSF) was used to repair Q235 steel pipes (Fe-Cr-C alloy was used as the cladding material). The effects of the welding current (WC), welding speed (WS), and laser shock frequency (LSF) on the geometry and microhardness of the weld bead were studied. The AW-LSF and AW repair processes were compared. The results demonstrate that the bead width ( W ) and penetration depth ( D ) increase with the WC, while the weld height ( H ) decreases with the WC. The H, W, and D all decrease with the WS; W and D increase with the LSF; and H decreases with the LSF. As the WC increases, the hardness of the fusion zone (FZ) and partial fusion zone (PFZ) decreases significantly, while the hardness of the heat-affected zone (HAZ) remains nearly unchanged. As the WS increases, the hardness of the PFZ decreases, while the hardness of the FZ and HAZ remains nearly unchanged. With the increase of the LSF, the hardness of the PFZ, FZ, and HAZ increases. Compared with AW, the AW-LSF can reduce the cladded layer crystal grain size, increase the hardness, and improve the sliding wear resistance.